NIH workshop on human milk composition: summary and visions. Issue 3 (5th July 2019) - Casavale, Kellie O; Ahuja, Jaspreet K C; Wu, Xianli; Li, Ying; Quam, Julia; Olson, Richard; Pehrsson, Pamela; Allen, Lindsay; Balentine, Douglas; Hanspal, Manjit; Hayward, Deborah; Hines, Erin Pias; et al.
ABSTRACT: Nationally representative data from mother–child dyads that capture human milk composition (HMC) and associated health outcomes are important for advancing the evidence to inform federal nutrition and related health programs, policies, and consumer information across the governments in the United States and Canada as well as in nongovernment sectors. In response to identified gaps in knowledge, the National Institute of Diabetes and Digestive and Kidney Diseases of the NIH sponsored the "Workshop on Human Milk Composition—Biological, Environmental, Nutritional, and Methodological Considerations" held 16–17 November 2017 in Bethesda, Maryland. Through presentations and discussions, the workshop aimed to 1 ) share knowledge on the scientific need for data on HMC; 2 ) explore the current understanding of factors affecting HMC; 3 ) identify methodological challenges in human milk (HM) collection, storage, and analysis; and 4 ) develop a vision for a research program to develop an HMC data repository and database. The 4 workshop sessions included 1 ) perspectives from both federal agencies and nonfederal academic experts, articulating scientific needs for data on HMC that could lead to new research findings and programmatic advances to support public health; 2 ) information about the factors that influence lactation and/or HMC; 3 ) considerations for data quality, including addressing sampling strategies and the complexities in standardizing collection, storage, and analyses of HM; and 4 ) insights on how existing research programs and databases can inform potential visions for HMC initiatives. The general consensus from the workshop is that the limited scope of HM research initiatives has led to a lack of robust estimates of the composition and volume of HM consumed and, consequently, missed opportunities to improve maternal and infant health.